(untitled) (The Research of Medical Science Review, 2025)
Background: Asthma is one of the most common chronic conditions affecting children and a leading cause of pediatric hospital readmissions worldwide. Inadequate caregiver education at discharge is a significant contributor to poor asthma management and early readmissions. Nurse-led discharge education has emerged as a promising strategy to improve patient outcomes by enhancing caregiver knowledge and preparedness. Aim: This study aimed to assess the correlation between nurse-led discharge education and 30-day hospital readmission rates in children with asthma at Lady Reading Hospital, Peshawar. Methods: A descriptive correlational study design was used, involving 270 children aged 2–12 years who were admitted with asthma and later discharged from the pediatric ward. The sample size was calculated using OpenEpi with a 95% confidence level and 5% margin of error. Participants were selected through non-probability convenience sampling. Data were collected through hospital records and structured caregiver interviews during follow-up within 30 days post-discharge. The data were analyzed using SPSS version 27, applying descriptive statistics and Chi-square tests to determine associations. Results: Among the 270 participants, 178 (65.9%) received nurse-led discharge education, and 92 (34.1%) did not. The overall 30-day readmission rate was 22.6%. Children who received discharge education had a significantly lower readmission rate (12.9%) compared to those who did not (41.3%). The association was statistically significant (χ² = 28.47, p < 0.001). Conclusion: Nurse-led discharge education is significantly associated with reduced 30-day readmission rates in children with asthma. Structured education should be integrated into routine discharge planning to enhance pediatric asthma outcomes.